“Slumming in Whitechapel” with Lillie Harris (1863–1921): Disembodiment, Power, and the Female Investigative Journalist - Van Remoortel, Marianne; Demarée, Fien (Victorian periodicals review, 2020)
This essay engages with Margaret Beetham’s ideas about embodiment, disembodiment, and power in relation to print to explore a series of anonymous articles entitled “Slumming in Whitechapel,” published in the Sheffield Weekly Telegraph between October 27 and November 17, 1888, at the height of the Jack the Ripper case. Combining biographical research into the life and career of the unnamed author, Lillie Harris (1863–1921), with in-depth textual analysis of the four articles, it argues that Harris’s embodiment of the female investigative journalist comes at a double cost, disembodying her as an individual and reducing the embodied working-class subjects of Whitechapel to objects.